Binding Energy of Exciton in Quantum Dots with the Central-cell Correction Depending on the Dot Sizes - Thao, To Thi; Viet, Nguyen Ai (Communications in Physics, 2007)
The binding energy of exciton in quantum dots with a parabolicconfinement potential was calculated by variational methods beyond the Kohn-Luttinger effective mass theory, when the central-cell correction was taken into account.We have assumed that a short range potential with two parameters for strength and range for exciton, representing the center-cell effect also depends on dot size. Our result is in good agreement with experiment.